THE EFFECT OF FREEZE-THAW CYCLES ON THE GEOTECHNICAL PROPERTIES OF CLAYEY SOIL TREATED WITH LIME - SALIH, NIHAD BAHAALDEEN; ABDALLA, TAVGA ARAM (Journal of Duhok University, 2021)
Fine-grained soils (cohesive soils) exposed to freezing-thawing cycles exhibit to notable alterations ontheir physical and mechanical characteristics. The environmental conditions' influences on soil geotechnical properties are significant, especially when stabilized by hydrated lime. This study was carried out to explore the effect of freeze-thaw cycles on cohesive soil stabilized by various hydrated lime percentages (zero%, 5%, 10%, and 15%) by dry mass, which cured for 28 days at 30°C. One-dimensional consolidations, unconfined strength, and shear box tests were performed for untreated and treated soil samples subjected to 0, 1, 2, and 3 freeze-thaw cycles. Duplication of freeze-thaw cycles significantly impacts some geotechnical properties and decreases them such as LL, UCS, Cc, Cr, and C. The PL and ϕvalues of the samples treated by hydrated lime and subjected to freeze-thaw cycles observed to be increased, which were due to the important role of hydrated lime addition. It is concluded that the hydrated lime can be effectively utilized to minimize the impacts of freeze-thaw periods on shear strength and compressibility of cohesive soil.